CHARACTERIZATION OF THE LEVELS OF MAJOR CHLORINATION BY-PRODUCTS IN DRINKING WATER SAMPLES - Borda Prada, Olga Lucía
THMs are one of the major by-products formed by the reaction of residual chlorine -which remains in water due to disinfection processes and naturally occurring organic matter. Their determination is of special interest in water resource management due to the toxicological risk associated with reproductive function and the possibility of generating cancer. In this research, the analysis of THMs Chloroform: CHCl3, chlorodibromomethane: CHClBr2, bromodichloromethane: CHCl2Br and tribromomethane: CHBr2, and the evaluation of their impact on water quality in a drinking water treatment plant located in the municipality of Cogua,one of the most important in the department of Cundinamarca, Colombia, which supplies about 170,0000 inhabitants. The analytical determination is carried out through the adaptation of a U.V-VIS spectrophotometric technique. The results obtained are correlated with the variables: residual chlorine, organic carbon, ultra violet absorbance at 254 nm and pH. On the other hand, thegeographic, morphological, hydric and spatial characterization of the area under study, area of influence and sampling points has been supported by the use of Geographic Information Systems (GIS)and mapping tools. The implementation of the phases that constitute the the research allowed reviewing the state of the art on chlorination by-products, as well as the characterization of the study area and identification of the sampling area, the adequacy of certain analytical parameters and the design of an application for the management of experimental data.